Budidaya Kepiting Soka Sistem RAS (Recirculating Aquaculture System) di Desa Tanjung Seloka Kecamatan Pulau Laut Selatan Kabupaten Kotabaru: Indonesia - Iskandar, Rina; Tony, Frans; Aminah, Aminah; Kisworo, Yulius (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
Tanjung Seloka Village in Kotabaru Regency has significant coastal resource potential, particularly in the aquaculture sector, with its superior commodity, soft-shelled crab, which has high economic value and stable market demand both domestically and internationally. This Community Service activity aims to improve the community's knowledge and skills in applying Recirculating Aquaculture System (RAS) technology to soft-shelled crab cultivation. The results of the activity indicate an increase in community understanding of the RAS system concept, the function of tools and materials, the benefits of implementing the technology, and the importance of water quality management in the cultivation process. In addition, the community's technical skills have also developed, particularly in preparing cultivation facilities, operating the RAS system, and carrying out maintenance during the soft-shelled crab cultivation process. This capacity increase indicates that RAS technology can be understood and implemented by the community as an alternative, more efficient and environmentally friendly cultivation innovation. The implication of this activity is the opening of opportunities for developing a sustainable technology-based soft-shelled crab cultivation business, which has the potential to increase productivity, expand business opportunities, and support the improvement of the welfare of the coastal community of Tanjung Seloka Village.